READING COMPREHENSION ABILITY OF GRADE V STUDENTS OF SDN 10 BANDA ACEH - Qariba, Farah; Mukhlis, Mukhlis; Tursinawati, Tursinawati (Elementary Education Research, 2024)
This research was motivated by the low ability to read and understand reading and the low learning outcomes of class V students at SD Negeri 10 Banda Aceh. The purpose of this research is to determine and examine reading comprehension abilities and the factors that cause difficulties in reading comprehension in class V students at SD Negeri 10 Banda Aceh. The approach in this research is descriptive qualitative with research subjects totaling 44 class V students at SD Negeri 10 Banda Aceh. Data obtained from interviews and tests. The results of the research show that the reading comprehension ability of class V students at SD Negeri 10 Banda Aceh is in the sufficient category, with an average of 51.13. It can be seen that the students' highest score is in the first indicator related to literal reading ability, while the students' lowest score in answering questions is in indicators 2, 3 and 4, namely related to interpretive understanding, critical understanding and creative understanding. There are 5 students who are in the very good category, 11 students who are in the good category, 15 students who are in the fair category, and 13 students who are in the poor category. The factors causing difficulty in reading comprehension in class V students at SD Negeri 10 Banda Aceh come from within and outside the student. Internal factors that influence are students' interest and daily activities in reading activities, and differences in students' abilities. Meanwhile, external factors are the facilities and infrastructure owned by students and the school and family environment.